2018
DOI: 10.1186/s12889-018-6236-5
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of energy drinks among adolescents in Norway: a cross-sectional study

Abstract: BackgroundEnergy drink (ED) consumption is increasing all over the world. We sought to describe the consumption of EDs among adolescents in Norway, and to explore the determinants of daily and high consumption.MethodsPopulation-based cross-sectional data were collected from a sample of 31,091 secondary school students in grade 8–13 aged 12–19 years. School grade, residency, socioeconomic status (SES), physical activity and leisure screen time were included in multiple regression analyses, in order to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
46
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 30 publications
18
46
1
1
Order By: Relevance
“…Our results indicated that for boys and girls, adolescents consuming soft drinks daily, alcohol weekly, with high screen time or with late bedtimes were more likely to consume ED more than once a week. These findings are consistent with previous cross-sectional studies conducted among adolescents which identified positive associations between ED consumption and consumption of other sugarsweetened beverages, 16 alcohol consumption, 5,11,14,28 screen use, 13,15,16 and late bedtime 17 or short sleep duration. 5,29,30 Association between ED consumption and alcohol use may be partially due to the fact of adolescents mixing both substances.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results indicated that for boys and girls, adolescents consuming soft drinks daily, alcohol weekly, with high screen time or with late bedtimes were more likely to consume ED more than once a week. These findings are consistent with previous cross-sectional studies conducted among adolescents which identified positive associations between ED consumption and consumption of other sugarsweetened beverages, 16 alcohol consumption, 5,11,14,28 screen use, 13,15,16 and late bedtime 17 or short sleep duration. 5,29,30 Association between ED consumption and alcohol use may be partially due to the fact of adolescents mixing both substances.…”
Section: Discussionsupporting
confidence: 92%
“…1 Similarly, both presence and absence of association between ED consumption, and socio-economic status, 11e14 family structure 11,12,14 or ethnicity 1 have been reported previously. Regarding lifestyle characteristics, higher ED consumption has been associated with higher screen time, 13,15,16 higher 1 or lower 15 physical activity, shorter sleep duration, 17 and higher alcohol and substance use. 1 To our knowledge, no study has specifically investigated sex differences in the patterns of ED consumption among adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, ED consumption was higher among students who were male, lived in broken families, consumed coffee and carbonated beverages, or had irregular sleep patterns. The present study revealed that being male was a prominent risk factor for ED consumption, similar to results of previous literature (4,26,27). In addition, misbeliefs about ED, that ED is not unhealthy, not have addictive effects, were found to be factors affecting the frequency of use.…”
supporting
confidence: 90%
“…A study conducted in the UK found that ED consumption had increased by 155% between 2006 and 2014 (25). Studies conducted in the United States, Norway, and Portugal determined that the frequency of ED consumption was between 33% and 56.7% (4,26,27). The Turkish Food Codex Communiqué on Energy Drinks recommends not allowing children to consume EDs (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation